1998
DOI: 10.1016/s0002-9440(10)65695-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SYT-SSX Fusion Transcripts in Synovial Sarcoma by Reverse Transcription-Polymerase Chain Reaction Using Archival Paraffin-Embedded Tissues

Abstract: The reciprocal translocation t(X;18)(p11;q11) is known to be highly characteristic of synovial sarcoma, and its consequence, an SYT-SSX fusion gene, is expected to be a diagnostic molecular marker. In this study, we conducted a reverse transcription-polymerase chain reaction-based assay to detect the SYT-SSX fusion gene transcripts using archival formalin-fixed, paraffin-embedded tumor specimens from a series of 32 synovial sarcoma cases including 6 tumors found in unusual anatomical sites. The SYT-SSX fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
96
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 18 publications
(9 reference statements)
1
96
1
1
Order By: Relevance
“…The RNA yield was more than adequate from all FNA samples. All RT-PCRs were carried out on prospective fresh samples in our study although the SYT-SSX fusion transcript may be demonstrated from archival paraffin-embedded tissues 2,19 and archival cytology material in up to 90% cases. 19 Moreover additional prognostic information may be obtained if one further categorizes the transcript as SYT-SSX1 or of SYT-SSX2 types.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA yield was more than adequate from all FNA samples. All RT-PCRs were carried out on prospective fresh samples in our study although the SYT-SSX fusion transcript may be demonstrated from archival paraffin-embedded tissues 2,19 and archival cytology material in up to 90% cases. 19 Moreover additional prognostic information may be obtained if one further categorizes the transcript as SYT-SSX1 or of SYT-SSX2 types.…”
Section: Discussionmentioning
confidence: 99%
“…At present, 3 different types of translocations have been identified in SS, involving SSX1, SSX2 (Crew et al, 1995;de Leeuw et al, 1995) and SSX4 . A strong association between SYT-SSX fusion type and morphology has been documented (Kawai et al, 1998;Nilsson et al, 1999;Antonescu et al, 2000), even if exceptions occur (Crew et al, 1995;Kashima et al, 1997;Tsuji et al, 1998;Mancuso et al, 2000).…”
mentioning
confidence: 96%
“…As the SYT-SSX fusion gene is actively transcribed, standard reverse-transcriptase polymerase chain reaction (RT-PCR) methods have been developed to specifically detect the chimeric mRNA in tissue biopsies of SS. [7][8][9][10][11][12][13][14] To …”
mentioning
confidence: 99%
“…5,10,11 However, exact determination of the SYT-SSX type in SS is more aptly determined by molecular approaches. As the SYT-SSX fusion gene is actively transcribed, standard reverse-transcriptase polymerase chain reaction (RT-PCR) methods have been developed to specifically detect the chimeric mRNA in tissue biopsies of SS.…”
mentioning
confidence: 99%
See 1 more Smart Citation